The Bidimensional Model of Mental Health: an empirical approach in a general population sample - González, Manuel (2023)
Background: Comprehensive mental health research is proposed as an important resource for individual well-being, as opposed to indicators of psychopathology. Objectives: We present an approach to the Bidimensional Model of Mental Health (BDSM) that considers psychological distress and subjective well-being as two separate but related dimensions. Methods: In a sample of 290 adults from the community, with 55.2% women and a mean age of 28.6 (Dt = 12.0). Results: The continuous results confirm a two-dimensional structure of psychopathology (PS) and subjective well-being (BS). The proposed model proposes classification into four groups according to the above result, namely, complete mental health (high BS, low PS, 62.2%), vulnerable (low BS, low PS, 11.4%), symptomatic but content (high BS, high PS, 11.4%) and troubled (low BS, high PS, 15%). The categorical results indicate that the problem and symptomatic groups obtained higher mean scores in trait worry, experiential and behavioral avoidance, and in turn, the symptomatic group scored higher in resistance to distress and in the more adaptive cognitive emotional regulation strategies; on the contrary, the vulnerable group obtained lower means in the latter. The results of the vulnerable and symptomatic groups confirm the coexistence of well-being and psychopathology. Conclusions: The promotion of subjective well-being is proposed when considering health in a more comprehensive way, because of its potential to generate profound and lasting benefits for individuals and the community in general.